KARAKTERISTIK PERILAKU MALSUAI SISWA PENGHUNI AREA PROSTITUSI (Studi Kasus Siswa SMPN2 Limpung Batang) - *, Maskur (Jurnal Penelitian, 2013)
The focus of this study is on the negative behavior of the students that appear to hamper their adjustment ability. Deviant behavior arises from ineffective behavior to deviant behavior inappropriate performed by them, both from the social regulations and religious norms. Self reporting, self-disclosure, and interviews were used to obtain the data. Observations were also carried out to observe the physiological reactions, action subject spontaneity that occurred outside the control of the subject, due to mental stress or feeling, as a subject of psychological phenomena. Descriptive-interpretative analysis, as teoritized by Milles and Huberman, was used to analyze the data. This research found that 51 of the 83 students who lived in the area of prostitution still had a positive self-adjustment capability, although residing around or near the area of prostitution. While the rest (32 students) had various problem to adjust their behavior to the school code of conduct, social norms and religious norms. Their deviant behavior appeared in truant behavior. becoming a helper on a truck until cross the province, smoking, rough with friends and teachers, consumption of liquor and dextro pills, like dealing with spirits, search pander prostitutes, to do free sex . The factors that affected the appearance of their deviant behavior was their parents' behavior that was often out of control, as well as family members. Environment and school friends and networks outside the school also became a strong factor influencing the emergence deviant behavior.